The effect of an online support group on patients׳ treatment decisions for localized prostate cancer: an online survey - Huber, Johannes; Friederich, Hans-Christoph; Herzog, Wolfgang; Ihrig, Andreas (Urologic oncology, 2017)
Objective: To analyze the effect of an online support group (OSG) on the final treatment decision for localized prostate cancer. Methods: We performed a cross-sectional descriptive study of the largest German prostate cancer OSG between July and October 2013. The online survey comprised 127 questions covering sociodemographic and disease-related information, decision-making habits, health-related quality of life, distress, depression, and anxiety. The primary outcome was to measure the effect of an OSG on the final treatment decision. Results: We analyzed the completed questionnaires from 686 patients with prostate cancer, 200 (29.2%) of whom revised their initial treatment decision. After revising their decisions, these patients more frequently underwent external beam radiation therapy (44.5% vs. 36.4%, P = 0.048) and active surveillance (10.5% vs. 3.7%, P<0.001) and less frequently underwent radical prostatectomy (52.5% vs. 74.9%, P<0.001). Engaging longer in the OSG, demanding a more active role in the decision-making process, and participating in a conventional support group were independently associated with revision of the initial treatment decision. Conclusions: Of all patients participating in the OSG, 29.2% revised their initial treatment decision. We estimate that this phenomenon may affect 17,000 patients with prostate cancer in the United States of America every year. This finding highlights the importance of OSGs for the health care system. The patient׳s desired degree of involvement in decision-making should be routinely clarified to adjust counseling accordingly.
Available online 31 October 2016
Gesehen am 13.09.2018